Education 4.0 and 21st Century Skills: A Case Study with Robotics Activities in Classroom - Messias, Glaucio; Rodrigues, Ueliton; Braga, Luis; Nakamura, Walter; Ferreira, Bruna; Paiva, Alex; Valentim, Natasha (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2018)
One of the most researched topics in Education 4.0 is the use of robotics in education. In this paper, we performed a case study related to skills developed for Education 4.0 through robotics activities, without involving competition. Students followed the process suggested by LEGO Education Maker and answered a self-assessment questionnaire about their developed skills and participated in a focus group. The teacher also reported her perceptions about the developed skills. We performed a qualitative analysis and the results indicated that robotics activities helped students to develop some skills, but it is still necessary to propose new approaches that will support students more in robotics activities.